Self-regulated Learning Mahasiswa Pendidikan Guru Sekolah Dasar (PGSD) Tahun Pertama - Darmiany Darmiany (Program Studi bimbingan Konseling PPs UNM Makassar, 2016)
The research is aimed to measure the comprehension level toward regulated learning of the students who are in the first year of prospective teacher related with the GPA (Grade Point Average) achieved. The research applied desciptive research method, and the data collection was done using survey towards 75 students which is 13% percents from the population, the PGSD Semester II students in FKIP of Semarang University. The findings showes that comprehension level of SRL of the PGSD students who are in their first year was 72% (the comprehension level of SRL was high), and there were positive effect between self-regulated learning (SRL) and GPA (Grade point Average) of the students. The higher the comprehension level towards the SRL the higher GPA will be achieved.